Measurement of residual stresses with optical techniques - Ribeiro, J.E. (2010)
The goal of this work was the development of other experimental techniques to measure residual stresses, as an alternative to the hole-drilling method with strain gauges. The proposed experimental techniques are based on the use of Moiré interferometry and in-plane electronic speckle pattern interferometry (ESPI). Both are field techniques allowing the assessment of in-plane displacements without contact and high resolution. Grating replication techniques were developed to record high-quality diffraction gratings onto the specimen's surfaces. An optical set-up of laser interferometry was developed to generate the master grating (virtual). An in-plane ESPI set-up was also designed and implemented to measure displacements in one direction. The stress relaxation was promoted by the blind hole-drilling and the obtained fringe patterns (Moiré and speckle) were video-recorded. Image processing techniques were applied to assess the in-plane strain field. A finite-element code (ansys®) was used to simulate the stress relaxation process, whose values were compared with the experimental data, and to calculate the hole-drilling calibration constants.